BERKOMUNIKASI DENGAN KEBENARAN: Terhadap Kebiasaan Menyebarkan Hoaks dan Berbohong di Media Sosial - Pradana, Mikael Galih (UNIKA Santo Thomas, 2024)
The emergence of social media has transformed the communication landscape, enabling rapid information exchange but also carrying serious risks related to the spread of hoaxes and fakenews. The Church, as a moral institution, responds to this phenomenon by prioritizing truth and honesty incommunication. In addressing this challenge, the Church presents a theological perspective emphasizing the importance of maintaining communication integrity and affirmingthe value of truth as a fundamental principle. Pope Francis highlights the importance of usingthe internet and social media wisely, preserving ethics and morality. Communication ethicsbecomes a crucial focus in the context of social media, with an emphasis on the principle oftruth correspondence and avoiding the spread of hoaxes. The Church’s theological messageasserts that lies damage human relationships with God and others, and warns of its social and spiritual consequences. The example of Jesus Christ inspires Christians to live in truth and communicate with love and justice. Through the guidance of the Holy Spirit, Christians are expected to express truth with courage and wisdom. Thus, the Church offers a holistic view and moral solutions in addressing the problem of hoaxes and falsehoods spread on social media.